The Students’ Voice: Perceptions of Senior Secondary School Students on the Efficacy of Web-Based Learning Application in Learning Commerce - Usman, Mariam Omosalewa; Akinpelu, Biodun; Akindoju, Olugbenga Gabriel (Journal of Education and Learning Research, 2025)
This study investigates the perception of students on the effect of a web-based instructional application (WBIA) on Lagos State senior secondary school students’ academic achievement in commerce. This study employs a qualitative method of research and one research question was raised to guide it. The study focuses on senior secondary school II Commerce students in Lagos State, Nigeria. A convenience sampling technique was employed to select the representative sample schools. A Web-Based Instructional Application was developed for the purpose of this study to teach commerce. Ten students were randomly chosen for the interview after the intervention. A Web-Based Instructional Application Interview Guide (WBIAIG) was used to collect data for this study and was validated.The recorded interview was verbatim transcribed to analyze the qualitative data. The qualitative findings of students’ responses to the interview reflect the positive perception regarding the use of the web-based instructional application for teaching commerce. The application appeared to enhance engagement, accessibility, and understanding of commerce topics, making learning more enjoyable and effective for the students. It is therefore recommended that students should be encouraged to use the application for self-paced learning, revision, and interactive practice to deepen their understanding of Commerce.